2008
DOI: 10.1021/np7007297
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin and Rutin as Potential Sunscreen Agents: Determination of Efficacy by an in Vitro Method

Abstract: Given that flavonoids are known for their ultraviolet (UV)B photoprotective properties in plants that contain them, we chose to study quercetin (1) and rutin (2) as agents that could potentially be used in sunscreen products. These two substances proved to behave in similar ways. When incorporated in oil-in-water emulsions, at a concentration of 10% (w/w), 1 and 2 give sun protection factor (SPF) values similar to that of homosalate, a standard substance. These two flavonoids also provided a non-negligible lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
0
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(108 citation statements)
references
References 15 publications
5
93
0
10
Order By: Relevance
“…Antioxidant phenolics also exhibit sun protection efficacy 23 in particular ferulic, caffeic and rosmarinic acid and quercetin, which are highlighted as new photoprotective agents for topical application products including cosmetics 15,24,25 . To widen the Passion fruit seed application, sun protection efficacy was further monitored.…”
Section: Resultsmentioning
confidence: 99%
“…Antioxidant phenolics also exhibit sun protection efficacy 23 in particular ferulic, caffeic and rosmarinic acid and quercetin, which are highlighted as new photoprotective agents for topical application products including cosmetics 15,24,25 . To widen the Passion fruit seed application, sun protection efficacy was further monitored.…”
Section: Resultsmentioning
confidence: 99%
“…The highest concentrations are found in onion [57]. Quercetin and rutin were tested as potential topical sunscreen factors in human beings and found to provide protection in the UVA and UVB range [65].…”
Section: Phytochemicals Skin Cancer and Rosmentioning
confidence: 99%
“…Literature survey has reported that flavonoids like flavonols 14,15,16] (quercetin, rutin, kaempferol, myricetin, fisetin, vitexin) flavones (apigenin, luteolin) flavanones (naringenin, hesperitn, naringin, and hesperidin), isoflavones 17 originally found at the seashores. Flowers are white in color, 20 fragrant at night and have reddish anthers.…”
Section: Introductionmentioning
confidence: 99%